Find $\int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}$
Answer
Verified
507k+ views
Hint: Use the formula for integration by parts,
\[\int{u(x)\cdot v(x)dx}=u(x)\cdot \int{v(x)dx}-\int{\left( \dfrac{d}{dx}u(x)\cdot \int{v(x)dx} \right)dx}\] with $u(x)=\ln x$ and $v(x)=\dfrac{1}{{{x}^{2}}}$.
Complete step-by-step answer:
First, let us decompose the function that we have to find the integration of (the integrand) into two functions.
Thus, $\int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\int\limits_{1}^{2}{\left( \ln x \right)\cdot \left( \dfrac{1}{{{x}^{2}}} \right)dx}$
We do this so that now we have two different functions and each of these functions is a simple function. Now, since we have 2 different functions, we can use integration by parts to solve the required integration. Using the ILATE rule for integration by parts, we can apply the formula\[\int{u(x)\cdot v(x)dx}=u(x)\cdot \int{v(x)dx}-\int{\left( \dfrac{d}{dx}u(x)\cdot \int{v(x)dx} \right)dx}\].
In the above formula, by the ILATE rule, the function $u(x)=\ln x$ and $v(x)=\dfrac{1}{{{x}^{2}}}$.
Using these in the formula,
\[\int{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( \ln x \right)\cdot \int{\dfrac{1}{{{x}^{2}}}dx}-\int{\left( \dfrac{d}{dx}\left( \ln x \right)\cdot \int{\dfrac{1}{{{x}^{2}}}dx} \right)dx}\ \ \ \ \ \ \ \ldots \left( 1 \right)\]
We know that \[\dfrac{d}{dx}\left( \ln x \right)=\dfrac{1}{x}\] and we can find \[\int{\dfrac{1}{{{x}^{2}}}dx}\] as follows:
\[\int{\dfrac{1}{{{x}^{2}}}dx}=\int{{{x}^{-2}}dx}\]
\[\begin{align}
& \Rightarrow \int{\dfrac{1}{{{x}^{2}}}dx}=\dfrac{{{x}^{-2+1}}}{-1} \\
& \Rightarrow \int{\dfrac{1}{{{x}^{2}}}dx}=\dfrac{-1}{x} \\
\end{align}\]
Using the values of \[\dfrac{d}{dx}\left( \ln x \right)=\dfrac{1}{x}\] and \[\int{\dfrac{1}{{{x}^{2}}}dx}=\dfrac{-1}{x}\] in the equation (1)
\[\begin{align}
& \int{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( \ln x \right)\cdot \left( \dfrac{-1}{x} \right)-\int{\left( \left( \dfrac{1}{x} \right)\cdot \left( \dfrac{-1}{x} \right) \right)dx} \\
& \Rightarrow \int{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( \dfrac{-\ln x}{x} \right)-\int{\left( \dfrac{-1}{{{x}^{2}}} \right)dx} \\
& \Rightarrow \int{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( \dfrac{-\ln x}{x} \right)+\int{\dfrac{1}{{{x}^{2}}}dx}\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ldots \left( 2 \right) \\
\end{align}\]
Using the value of \[\int{\dfrac{1}{{{x}^{2}}}dx}=\dfrac{-1}{x}\] in equation (2),
\[\begin{align}
& \int{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( \dfrac{-\ln x}{x} \right)+\left( \dfrac{-1}{x} \right)\ \\
& \Rightarrow \int{\dfrac{\ln x}{{{x}^{2}}}dx}=-\dfrac{\ln x}{x}-\dfrac{1}{x}+C \\
\end{align}\]
Putting in the lower and upper limit in the integration obtained,
\[\begin{align}
& \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( -\dfrac{\ln x}{x}-\dfrac{1}{x} \right)_{1}^{2} \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( -\dfrac{\ln 2}{2}-\dfrac{1}{2} \right)-\left( -\dfrac{\ln 1}{1}-\dfrac{1}{1} \right) \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( -\dfrac{\ln 2}{2}-\dfrac{1}{2} \right)-\left( 0-1 \right) \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( -\dfrac{\ln 2}{2}-\dfrac{1}{2} \right)-\left( -1 \right) \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=-\dfrac{\ln 2}{2}-\dfrac{1}{2}+1 \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=-\dfrac{\ln 2}{2}+\dfrac{1}{2} \\
\end{align}\]
\[\begin{align}
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\dfrac{1}{2}-\dfrac{\ln 2}{2} \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\dfrac{1-\ln 2}{2} \\
\end{align}\]
Thus the required integration of $\int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}$ is \[\dfrac{1-\ln 2}{2}\].
Note: At first sight of the question, a student may be tempted to use integration by substitution method and apply $\ln x=t$ because the differentiation of $\ln x=\dfrac{1}{x}$ is there in the question. But because of the square attached, this approach fails to give the correct answer. Had the question been $\int\limits_{1}^{2}{\dfrac{\ln x}{x}dx}$, in that case, such an approach would have provided the correct results but because of ${{x}^{2}}$ in the denominator, integration by parts is the more suitable approach for finding the correct answer.
\[\int{u(x)\cdot v(x)dx}=u(x)\cdot \int{v(x)dx}-\int{\left( \dfrac{d}{dx}u(x)\cdot \int{v(x)dx} \right)dx}\] with $u(x)=\ln x$ and $v(x)=\dfrac{1}{{{x}^{2}}}$.
Complete step-by-step answer:
First, let us decompose the function that we have to find the integration of (the integrand) into two functions.
Thus, $\int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\int\limits_{1}^{2}{\left( \ln x \right)\cdot \left( \dfrac{1}{{{x}^{2}}} \right)dx}$
We do this so that now we have two different functions and each of these functions is a simple function. Now, since we have 2 different functions, we can use integration by parts to solve the required integration. Using the ILATE rule for integration by parts, we can apply the formula\[\int{u(x)\cdot v(x)dx}=u(x)\cdot \int{v(x)dx}-\int{\left( \dfrac{d}{dx}u(x)\cdot \int{v(x)dx} \right)dx}\].
In the above formula, by the ILATE rule, the function $u(x)=\ln x$ and $v(x)=\dfrac{1}{{{x}^{2}}}$.
Using these in the formula,
\[\int{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( \ln x \right)\cdot \int{\dfrac{1}{{{x}^{2}}}dx}-\int{\left( \dfrac{d}{dx}\left( \ln x \right)\cdot \int{\dfrac{1}{{{x}^{2}}}dx} \right)dx}\ \ \ \ \ \ \ \ldots \left( 1 \right)\]
We know that \[\dfrac{d}{dx}\left( \ln x \right)=\dfrac{1}{x}\] and we can find \[\int{\dfrac{1}{{{x}^{2}}}dx}\] as follows:
\[\int{\dfrac{1}{{{x}^{2}}}dx}=\int{{{x}^{-2}}dx}\]
\[\begin{align}
& \Rightarrow \int{\dfrac{1}{{{x}^{2}}}dx}=\dfrac{{{x}^{-2+1}}}{-1} \\
& \Rightarrow \int{\dfrac{1}{{{x}^{2}}}dx}=\dfrac{-1}{x} \\
\end{align}\]
Using the values of \[\dfrac{d}{dx}\left( \ln x \right)=\dfrac{1}{x}\] and \[\int{\dfrac{1}{{{x}^{2}}}dx}=\dfrac{-1}{x}\] in the equation (1)
\[\begin{align}
& \int{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( \ln x \right)\cdot \left( \dfrac{-1}{x} \right)-\int{\left( \left( \dfrac{1}{x} \right)\cdot \left( \dfrac{-1}{x} \right) \right)dx} \\
& \Rightarrow \int{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( \dfrac{-\ln x}{x} \right)-\int{\left( \dfrac{-1}{{{x}^{2}}} \right)dx} \\
& \Rightarrow \int{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( \dfrac{-\ln x}{x} \right)+\int{\dfrac{1}{{{x}^{2}}}dx}\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ldots \left( 2 \right) \\
\end{align}\]
Using the value of \[\int{\dfrac{1}{{{x}^{2}}}dx}=\dfrac{-1}{x}\] in equation (2),
\[\begin{align}
& \int{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( \dfrac{-\ln x}{x} \right)+\left( \dfrac{-1}{x} \right)\ \\
& \Rightarrow \int{\dfrac{\ln x}{{{x}^{2}}}dx}=-\dfrac{\ln x}{x}-\dfrac{1}{x}+C \\
\end{align}\]
Putting in the lower and upper limit in the integration obtained,
\[\begin{align}
& \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( -\dfrac{\ln x}{x}-\dfrac{1}{x} \right)_{1}^{2} \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( -\dfrac{\ln 2}{2}-\dfrac{1}{2} \right)-\left( -\dfrac{\ln 1}{1}-\dfrac{1}{1} \right) \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( -\dfrac{\ln 2}{2}-\dfrac{1}{2} \right)-\left( 0-1 \right) \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\left( -\dfrac{\ln 2}{2}-\dfrac{1}{2} \right)-\left( -1 \right) \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=-\dfrac{\ln 2}{2}-\dfrac{1}{2}+1 \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=-\dfrac{\ln 2}{2}+\dfrac{1}{2} \\
\end{align}\]
\[\begin{align}
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\dfrac{1}{2}-\dfrac{\ln 2}{2} \\
& \Rightarrow \int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}=\dfrac{1-\ln 2}{2} \\
\end{align}\]
Thus the required integration of $\int\limits_{1}^{2}{\dfrac{\ln x}{{{x}^{2}}}dx}$ is \[\dfrac{1-\ln 2}{2}\].
Note: At first sight of the question, a student may be tempted to use integration by substitution method and apply $\ln x=t$ because the differentiation of $\ln x=\dfrac{1}{x}$ is there in the question. But because of the square attached, this approach fails to give the correct answer. Had the question been $\int\limits_{1}^{2}{\dfrac{\ln x}{x}dx}$, in that case, such an approach would have provided the correct results but because of ${{x}^{2}}$ in the denominator, integration by parts is the more suitable approach for finding the correct answer.
Recently Updated Pages
Master Class 12 Social Science: Engaging Questions & Answers for Success
Master Class 12 Physics: Engaging Questions & Answers for Success
Master Class 12 Maths: Engaging Questions & Answers for Success
Master Class 12 English: Engaging Questions & Answers for Success
Master Class 12 Chemistry: Engaging Questions & Answers for Success
Master Class 12 Biology: Engaging Questions & Answers for Success
Trending doubts
Explain sex determination in humans with the help of class 12 biology CBSE
Give 10 examples of unisexual and bisexual flowers
Distinguish between asexual and sexual reproduction class 12 biology CBSE
How do you convert from joules to electron volts class 12 physics CBSE
Derive mirror equation State any three experimental class 12 physics CBSE
Differentiate between internal fertilization and external class 12 biology CBSE